Hydrogen diffusivities as a measure of relative dislocation densities in palladium and increase of the density by plastic deformation in the presence of dissolved hydrogen. (1st January 2015) - Deutges, Martin; Barth, Hans Peter; Chen, Yuzeng; Borchers, Christine; Kirchheim, Reiner
Graphical abstract: Abstract: The effect of dissolved hydrogen on the dislocation density in cold-rolled palladium was investigated in order to provide evidence of a line energy reduction caused by hydrogen–dislocation interaction as proposed by the defactant concept. For this issue, palladium samples were electrochemically charged with hydrogen and subsequently cold rolled. Using conventional methods (X-ray diffraction, transmission electron microscopy) and a newly developed diffusion method, it was shown that the dislocation density after deformation increases with increasing hydrogen concentration.